Research Progress on Trees and Shrubs of Economic Importance in Northeast Mexico - Maiti, Ratikanta; Rodrigues, Humberto Gonzalez (International Journal of Economic Plants, 2017)
The present paper present in brief summary of research advances undertaken by Dr. Maiti during the last four years as visiting research scientist in Forest Science Faculty, Universidad Autonoma de Nuevo Leon, Mexico. The research deals with morphology, branching pattern, anatomy, plant traits, few physiological-biochemical traits such leaf pigments, epicuticular wax, leaf macro and micronutrients, carbon sequestration. The results reveal that there exists a large variability among woody trees and shrubs (more than 30 species) in various morpho-anatomical and physiological and anatomical traits mentioned. These variations in different traits determine the adaptive capacity of the species in the semiarid regions of Northeast Mexico.